2021
DOI: 10.1016/j.xjtc.2020.12.039
|View full text |Cite
|
Sign up to set email alerts
|

Safety of perioperative cerebrospinal fluid drain as a protective strategy during descending and thoracoabdominal open aortic repair

Abstract: Objective: We present our experience with routine application of the cerebrospinal fluid (CSF) drain (CSFD) during open aortic repair.Methods: We retrospectively reviewed 100 patients with descending thoracic aortic aneurysm (DTAA) or thoracoabdominal aortic aneurysm (TAAA) or who underwent CSFD insertion before open repair between 2006 and 2017. All CSFDs were inserted by the cardiovascular anesthesia team. The goal was to keep intracranial pressure<10 mm Hg during the surgical procedure by draining CSF at a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…A pressure of ≤10 mm Hg was maintained during this period at surgeon discretion to alleviate symptoms. 24 Details of the evolution of our institutional SCI prevention protocol to its current form, including prescribed CSFD rates, are shown in Table E1 . 25 Anticoagulant medications were held for drain placement/removal according to a standardized protocol concordant with the American Society of Regional Anesthesia guidelines ( Online Data Supplement ).…”
Section: Methodsmentioning
confidence: 99%
“…A pressure of ≤10 mm Hg was maintained during this period at surgeon discretion to alleviate symptoms. 24 Details of the evolution of our institutional SCI prevention protocol to its current form, including prescribed CSFD rates, are shown in Table E1 . 25 Anticoagulant medications were held for drain placement/removal according to a standardized protocol concordant with the American Society of Regional Anesthesia guidelines ( Online Data Supplement ).…”
Section: Methodsmentioning
confidence: 99%
“… 39 Another very recent study that assessed the safety of perioperative CSFD placement came to similar conclusions. 40 A large meta-analysis performed to define a more accurate risk-benefit ratio analyzed 34 studies from 1990 to 2017 and included 4,714 patients who had CSFD placed for open or endovascular repairs of thoracic or thoracoabdominal aortic aneurysms. The study identified the overall CSFD-related complication rate at 6.5%, with severe complications occurring in 2.5% of the cases and a pooled CSFD-related mortality rate of 0.9%.…”
Section: Debatementioning
confidence: 99%
“…Prevention of SCI requires appropriate pre-operative risk assessment for the patients, as well as employing a combination of protective strategies peri-and postoperatively to ensure adequate perfusion of the spinal cord. These treatment adjuncts may include cerebrospinal fluid drainage Safety of cerebrospinal fluid drainage in descending and thoracoabdominal aortic replacement surgery (CSFD), motor evoked potential monitoring, left heart bypass, epidural cooling, and preoperative imaging to identify and preserve the artery of Adamkiewicz (7)(8)(9)(10)(11). The American College of Cardiology and American Heart Association designates a class IA level recommendation (12) for the use of CSFD for decreasing the incidence of temporary, as well as permanent SCI, in patients undergoing open thoracoabdominal aortic repair.…”
Section: Introductionmentioning
confidence: 99%